THE INFLUENCE OF NCT DREAM AS A BRAND IMAGE ON PURCHASING DECISIONS - Novia Widyasari; Bachri, Syamsul; Santi, Ira Nuriya (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2025)
This study explores the impact of NCT Dream as a brand ambassador and how brand image affects purchase intention, with purchase intention acting as a mediating variable among users of Somethinc beauty products. The research was conducted in Palu City. A quantitative approach with multiple regression analysis was employed. Data were collected via questionnaires distributed to 175 respondents, and primary data were obtained through purposive sampling. The respondents are Somethinc users who recognize NCT Dream as a brand ambassador. The findings indicate that (1) the Brand Ambassador has a positive and significant effect on Purchase Intention; (2) Brand Image positively and significantly influences Purchase Intention; (3) the Brand Ambassador has a positive and significant effect on Purchasing Decisions; (4) Brand Image also positively and significantly affects Purchasing Decisions; (5) Purchase Intention significantly and positively impacts Purchasing Decisions; (2) Purchase Intention mediates the influence of the Brand Ambassador on Purchasing Decisions; and (7) Purchase Intention mediates the effect of Brand Image on Purchasing Decisions. Companies can boost sales by leveraging brand ambassadors and improving brand image, thereby increasing consumer interest and purchase decisions.